2022
DOI: 10.1039/d2dt02068h
|View full text |Cite
|
Sign up to set email alerts
|

Comparative NMR metabolomics of the responses of A2780 human ovarian cancer cells to clinically established Pt-based drugs

Abstract: Pt-based drugs play a very important role in current cancer treatments; yet, their cellular and mechanistic aspects are not fully understood. NMR metabolomics provides a powerful tool to investigate the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…18,19 It follows that the behaviour of these cytotoxic gold compounds largely differs from established anticancer platinum(II) drugs that were earlier reported to produce relatively modest metabolic alterations in the same cancer cell line, possibly due to their prevalent DNA damaging mechanism. 14 Finally, this study further demonstrates that NMR metabolomics is a powerful and effective tool to disclose the metabolic effects of anticancer metallodrugs offering the chance to establish valuable correlations between the main mechanistic aspects and the observed metabolic alterations.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…18,19 It follows that the behaviour of these cytotoxic gold compounds largely differs from established anticancer platinum(II) drugs that were earlier reported to produce relatively modest metabolic alterations in the same cancer cell line, possibly due to their prevalent DNA damaging mechanism. 14 Finally, this study further demonstrates that NMR metabolomics is a powerful and effective tool to disclose the metabolic effects of anticancer metallodrugs offering the chance to establish valuable correlations between the main mechanistic aspects and the observed metabolic alterations.…”
mentioning
confidence: 66%
“…15 Moreover, in line with AF, both gold carbenes induce a signicant reduction of the UDP sugars (UDP-acetylglucosamine and UDP-galactosamine). Interestingly, a signicant decrement of these molecules was also observed in A2780 cells upon platinum drugs treatment 14 and was related to a reduction of cancer aggressiveness 16 and ER stress. 17 In conclusion, NMR metabolomics has revealed that these gold carbene compounds induce relevant and specic alterations in the cancer cell metabolome that are signicantly different from those induced by AF.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…While carboplatin may share some of its antitumoral activity with oxaliplatin, it also has specific mechanisms of action and yields negligible neurotoxicity. 16,17 Hence, the use of carboplatin-containing chemotherapy could be relevant in patients with advanced PDAC, as previously reported in combination with gemcitabine, 18 and in other pancreatic neoplasms including neuroendocrine carcinomas 19 and mucinous cystadenocarcinomas. 20 The aim of this study was to report the efficacy and tolerance of the LV5FU2-carboplatin combination in a large and comprehensive consecutive cohort patients with advanced PDAC after failure of standard chemotherapies.…”
Section: Introductionmentioning
confidence: 78%
“…As an example, some of us characterized the cellular effects induced in A2780 cells and A2780cis cells by treatment with the three clinically established platinum drugs, i.e., cisplatin, carboplatin, and oxaliplatin [21]. With the same methodological approach, we also addressed the cellular alterations caused by gold(I)-based drugs with optimal anticancer properties [22][23][24].…”
Section: Introductionmentioning
confidence: 99%